MEREGUK KEDAMAIAN DALAM PERKAWINAN SATU AGAMA - Achmad Rosidi (Harmoni, 2015)
This study employs analytical descriptive design with qualitative approach. The study aims to describe factors of interfaith marriage and obtain the information related to society opinion, religious leaders, and the government toward interfaith marriage. The result of the study shows that interfaith marriage is a trend recently. It is published by mass media and society has different perspective to look at the interfaith marriage. They think that interfaith marriage can cause some potential problems such as their marriage and their children’ psyschology especially in deciding what religions they choose.